2019
DOI: 10.1167/iovs.18-25572
|View full text |Cite
|
Sign up to set email alerts
|

Selective Serotonin Reuptake Inhibitors Aggravate Depression-Associated Dry Eye Via Activating the NF-κB Pathway

Abstract: PURPOSE. Our study aimed to evaluate the side effects of selective serotonin reuptake inhibitors (SSRIs) on the ocular surface. METHODS. Twenty patients with depression and dry eye disease (DED) were randomly picked to receive SSRI treatment, whereas another 20 patients received placebo treatment. The serotonin, inflammatory cytokine, and proapoptotic protein levels were determined by using protein chip, qRT-PCR, and ELISA analyses. A rat depression model was established, and SSRIs were applied for 3 or 6 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 33 publications
2
55
0
1
Order By: Relevance
“…If refractive surgery is planned, it should be ensured that a patient's refractive status remains stable. A previous study reported that serotonin induces cell inflammation and apoptosis in corneal epithelial cells [27]. Since this effect may lead to changes in CD, the present research performed CD measurements by Pentacam HR, finding that SSRIs made no significant changes in anterior chamber parameters, LD or CD at the three-month follow-ups.…”
Section: Discussionmentioning
confidence: 60%
“…If refractive surgery is planned, it should be ensured that a patient's refractive status remains stable. A previous study reported that serotonin induces cell inflammation and apoptosis in corneal epithelial cells [27]. Since this effect may lead to changes in CD, the present research performed CD measurements by Pentacam HR, finding that SSRIs made no significant changes in anterior chamber parameters, LD or CD at the three-month follow-ups.…”
Section: Discussionmentioning
confidence: 60%
“…Experimental studies reflecting the incongruence of clinical outcomes hypothesize that an interplay between SSRIs and the quality of the environmental Fig. 8 Schematic representation that summarize the main effects of fluoxetine treatment cessation and ethanol drinking reinstatement on microglial morphology and its association with reactive phenotype (inflammatory response) in each brain region analyzed conditions (Alboni et al 2016(Alboni et al ,2017) may support the divergent effects of SSRI treatment on the inflammatory response (Tynan et al 2012;Horowitz et al 2014;Lu et al 2017;Zhang et al 2019). Regarding our findings on microglial morphology, fluoxetine treatment cessation induced subtle changes in main morphometric parameters that indicate higher spatial complexity (fractal dimension) and lower heterogeneity (lacunarity), as well as increases in process thickening and shortening (density and roughness), effects that are also more prominent in the striatum and hippocampal CA1.…”
Section: Discussionmentioning
confidence: 99%
“…However, conventional SSRI antidepressants fail to respond to immunotherapies involving depressive disorder, demonstrating no, anti- or even pro-inflammatory effects (Hannestad et al 2011 ; Kim et al 2013 ; Chen et al 2018 ; Tomaz et al 2020 ; Yoshimura et al 2013 ). Experimental studies reflecting the incongruence of clinical outcomes hypothesize that an interplay between SSRIs and the quality of the environmental conditions (Alboni et al 2016 , 2017 ) may support the divergent effects of SSRI treatment on the inflammatory response (Tynan et al 2012 ; Horowitz et al 2014 ; Lu et al 2017 ; Zhang et al 2019 ). Regarding our findings on microglial morphology, fluoxetine treatment cessation induced subtle changes in main morphometric parameters that indicate higher spatial complexity (fractal dimension) and lower heterogeneity (lacunarity), as well as increases in process thickening and shortening (density and roughness), effects that are also more prominent in the striatum and hippocampal CA1.…”
Section: Discussionmentioning
confidence: 99%
“…However, conventional SSRI antidepressants fail to respond to immunotherapies involving depressive disorder, demonstrating no, anti-or even pro-in ammatory effects [39][40][41]68,70]. Experimental studies re ecting the incongruence of clinical outcomes hypothesize that an interplay between SSRIs and the quality of the environmental conditions [35,71] may support the divergent effects of SSRI treatment on the in ammatory response [42,[72][73][74]. Regarding our ndings on microglial morphology, uoxetine treatment cessation induced subtle changes in main morphometric parameters that indicate higher spatial complexity (fractal dimension) and lower heterogeneity (lacunarity), as well as increases in process thickening and shortening (density and roughness), effects that are also more prominent in the striatum and hippocampal CA1.…”
Section: Discussionmentioning
confidence: 99%